Teaching-learning for diversity. An education pending in peruvian education - Coriñaupa Vargas, Francisco (2019)
To see the student as a unique being in every way, in any of its dimensions, is elementary to achieve learning, although today it is set up as a very difficult task taking into account the peculiarity of our current world and our country; But beyond the inherent difficulties of educating, that is the work of the teacher, who must see and help each of his students to discover the world of potentialities that has, always, beyond a label or a health or social condition. To learn to see the diversity of the group and accept the peculiarity of each student, will only be possible through a personal change, and by following a few steps that will help to see the only thing the student: observe and pre-deal, investigate, experience and build.